Forms of contract of forward ijarah and its applications in contemporary finance: An empirical juristic study / Amer Aldershewi - Amer, Aldershewi (2017)
One of the prevalent contracts carried out by Islamic banks is forward contract, which is applied in different forms, embodies differentarenas in contemporary financial services. The research aims to discourse the formulation of this contract in the light of Islamic jurisprudential heritage and to study the provisions and general maxims surrounding this contract for the purpose of having an accurate legal grounding and juristic formation. In addition, this study strives to analyse the permissibility of this contract in the schools of Islamic law particularly in Hanafi School, as it considers forward contract as illegal and restricts the lease to be specified. The School also explicates the contemporary applications of the forward contract in the banks and its specifications followed by an elucidation of its risks and resolutions. The researcher has adopted a library research method to collect various juristic opinions of the forward contract. The researcher has used comparative method. The researcher has defended on the various juristic opinions and their evidences followed by a discussion and therefore prefers one opinion to others. As part of field study, the researcher conducted interviews with bank officials to have better understanding about the application of this contract in Islamic banks. This study has reached to several significant findings; among them isthatthe four Sunni schools validates the forward contract and the payment has to be done on spot if Salam contract has been used as means of contract, which is unlike the Ijarah contract in whichinstalment is acceptable. Furthermore, a variable index can be used as rent indicative if it is reliable and based on definite knowledge and non-cash items, which are also accepted for payment, no matter whether they are properties like wheat and cloths or any other usufruct. However, the forward contract is not terminated due to destruction or damage of the subject matter. In this situation, the lessor has to recompense in lieu and the lessee is not liable if damage happened follows his normal or allowed use while he has to provide the financial coverage in the event of transgression and violation Finally, banks apply different forms under this contract such as as diminishing partnership, Ijarah muntahia bittamleek, Istisna, and banksdo not ask the tenant to pay the rent on spot instead it tolerates late payments.